An easy to construct sub-micron resolution imaging system - Lakhi Sharma (Nature Portfolio, 2020)
Abstract We report an easy to construct imaging system that can resolve particles separated by $$\ge $$ ≥ 0.68 $$\upmu $$ μ m with minimum aberrations. Its first photon collecting lens is placed at a distance of 31.6 mm giving wide optical access. The microscope has a Numerical Aperture (NA) of 0.33, which is able to collect signal over 0.36 sr. The diffraction limited objective and magnifier recollects 77% photons into the central disc of the image with a transverse spherical aberration of 0.05 mm and magnification upto 238. The system has a depth of field of 142 $$\upmu $$ μ m and a field of view of 56 $$\upmu $$ μ m which images a large ensemble of atoms. The imaging system gives a diffraction limited performance over visible to near-infrared wavelengths on optimization of the working distance and the distance between the objective and magnifier.